1971
DOI: 10.1042/cs0400089
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis in the Myocardiopathy and Muscular Dystrophy of the Syrian Hamster

Abstract: 1. Incorporation in vitro of l-[4,5-3H]leucine and l-[U-14C]lysine into a soluble protein fraction and into actomyosin of hearts, diaphragms and biceps femoris of an inbred strain of Syrian hamsters suffering from a hereditary myocardiopathy and muscular dystrophy was studied. 2. Incorporation of both amino acids was normal in myopathic hearts from hamsters aged 60–90 days but significantly elevated at 180–240 days of age. Their incorporation was higher in the myopathic diaphragm and biceps femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
0

Year Published

1971
1971
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…4). These results for soluble protein resemble those for soluble protein and for actomyosin after a short incubation of whole-cell preparations from diaphragm (Lochner et al, 1971) and for total protein of diaphragm (Goldspink & Goldspink, 1977). The labelling pattem of the microsomal protein of the diaphragm resembled that of the soluble protein, except that the labelling was higher than for the soluble protein.…”
Section: Determination Ofprotein and Radioactivitysupporting
confidence: 57%
See 1 more Smart Citation
“…4). These results for soluble protein resemble those for soluble protein and for actomyosin after a short incubation of whole-cell preparations from diaphragm (Lochner et al, 1971) and for total protein of diaphragm (Goldspink & Goldspink, 1977). The labelling pattem of the microsomal protein of the diaphragm resembled that of the soluble protein, except that the labelling was higher than for the soluble protein.…”
Section: Determination Ofprotein and Radioactivitysupporting
confidence: 57%
“…However, certain substances 'such as Ca2 +Mg2+dependent ATPase, calsequestrin and guanylate cyclase do not appear to be changed (Yap & MacLennan, 1976;Blosser & Appel, 1978). Whole cell preparations of dystrophic hamster hindleg muscle, incubated in vitro with labelled amino acids, exhibited an increased labelling of soluble proteins and of actomyosin at both 60 days and 180-240 days of age; similar changes in the heart and diaphragm occurred in the older age group (Lochner et al, 1971). In addition, the total proteins of the hypertrophied diaphragm of dystrophic hamsters, incubated in vitro, exhibited an increase in synthesis and a smaller increase in degradation (Goldspink & Goldspink, 1977).…”
mentioning
confidence: 91%
“…Specifically, since 1963 more than 79,000 articles have been published (PubMed Database) with use of or reference to the hamster. The hamster has been utilized to investigate pathological dysfunction stemming from diabetes mellitus (Sims and Landau 1967), hypoglycemia (Sodoyez et al 1969), muscular dystrophy (Lochner et al 1971), cardiomyopathy (Schwartz et al 1972), hypothermia (Resch and Musacchia 1976), emphysema (Karlinsky and Snider 1978), skeletal muscle transplantation (Faulkner et al 1983), age (Nichols and Borer 1987), chronic wasting infection (Drew et al 1988), skeletal muscle ischemia/reperfusion (Messina 1990), inactivity (Zhan and Sieck 1992), and gene therapy (Xiao et al 2000). Moreover, the hamster has been used to explore the physiological function of the myocardium (Aomine et al 1982), vasculature (Burns and Palade 1968), and skeletal muscle (Lossnitzer and Kelly 1968).…”
mentioning
confidence: 99%
“…Studies of creatine kinase in mouse muscular dystrophy have revealed the presence of an abnormal enzyme molecule lacking one of the two essential thiol groups of the normal dimeric enzyme (Hooton & Watts, 1966). Defects in sarcosomal oxidative phosphorylation have been detected at late stages of polymyopathy in the same Syrian hamster strain we have used for our studies (Lochner & Brink, 1967;Lochner et al, 1968;Schwartz et al, 1968). An abnormal foetal-type metmyoglobin has been detected in the muscles ofpatients with progressive muscular dystrophy (Whorton et al, 1961).…”
Section: Discussionmentioning
confidence: 89%